Elucidation of the Mechanism of Action of Ginseng Against Acute Lung Injury/Acute Respiratory Distress Syndrome by a Network Pharmacology-Based Strategy - Ding, Qi; Zhu, Wenxiang; Diao, Yirui; Xu, Gonghao; Wang, Lu; Qu, Sihao; Shi, Yuanyuan (Frontiers in Pharmacology, 2021)
Acute respiratory distress syndrome (ARDS) is a complex cascade that develops from acute lung injury (ALI). Ginseng can be used to treat ALI/ARDS. Studies have shown that some of ingredients in ginseng had anti-inflammation, anti-oxidative and immune-regulation effects, and can protect alveolar epithelial cells in mice. However, the potential targets, biological processes and pathways related to ginseng against ALI/ARDS have not been investigated systematically. We employed network pharmacology, molecular docking, and animal experiments to explore the therapeutic effects and underlying mechanism of action of ginseng against ALI/ARDS. We identified 25 compounds using ultra-high-performance liquid chromatography-Q-Orbitrap mass spectrometry and their 410 putative targets through database analyses. Sixty-nine of them were considered to be key targets of ginseng against ALI/ARDS according to overlapping with ALI/ARDS-related targets and further screening in a protein–protein interaction (PPI) network. The phosphatidylinositol 3-kinase-protein kinase B (PI3K-AkT) and mitogen-activated protein kinase (MAPK) pathways were recognized to have critical roles for ginseng in ALI/ARDS treatment. Signal transducer and activator of transcription (STAT)3, vascular endothelial growth factor A (VEGFA), fibroblast growth factor (FGF)2, phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA), MAPK1 and interleukin (IL)2 were the top-six nodes identified by analyses of a compound–target-pathway network. Molecular docking showed that most of the ingredients in ginseng could combine well with the six nodes. Ginseng could reduce the pathologic damage, neutrophil aggregation, pro-inflammatory factors, and pulmonary edema in vivo, and inhibit the PI3K-Akt signaling pathway and MAPK signaling pathway through downregulating expression of STAT3, VEGFA, FGF2, PIK3CA, MAPK1 and IL2. Our study provides a theoretical basis for ginseng treatment of ALI/ARDS.